Functional outcome after transperitoneal laparoscopic pyeloplasty at a tertiary care center, Nepal - Regmi, Prabodh; Bhattarai, Anu; Maharjan, Sagar; Basnet, Robin Bahadur (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Pyeloplasty is the gold standard surgical treatment for Pelvic-Ureteric Junction Obstruction (PUJO). Laparoscopic pyeloplasty has gained popularity in recent years because it is less invasive, has better cosmesis, and reduces hospital stays with an equivalent success rate compared to open pyeloplasty. This study was designed to find out the success rate of laparoscopic transperitoneal pyeloplasty in cases with unilateral PUJO.Method: This was a retrospective study, which included four years of data on patients who underwent laparoscopic pyeloplasty from 1 Jan 2019 to 31 Dec 2022 in the Department of Urology, Bir Hospital, National Academy of Medical Sciences, Nepal. Ethical approval was obtained. Microsoft Excel was used for descriptive analysis, frequency, and percentage of clinical and demographic data for age, gender, and site. Pre- and post-operative data of differential renal function (DRF) based on the radio-isotope renography and their association were compared using the χ2 test. A p-value of 30 y,  and a mean improvement of DRF of 4.3% was also observed in the cases with DRF ≤30%.Conclusion: The laparoscopic pyeloplasty showed excellent functional outcomes in the majority of the cases with PUJO.